Resveratrol decreases local inflammatory markers and systemic endotoxin in patients with aggressive periodontitis. Issue 25 (24th June 2022) - Zhang, Qiang; Xu, Shuhan; Xu, Wenxiu; Zhou, Yang; Luan, Hairong; Wang, Deli
Abstract: Background: Inflammation is hypothesized to contribute to the pathogenesis of periodontitis. Resveratrol (RV) is known for its anti-inflammatory properties. The purpose of this study was to investigate the inhibitory effect of RV on local inflammatory markers and systemic endotoxin in patients with periodontitis. Methods: A total of 160 patients with periodontitis were enrolled in this study. The selected patients were randomly divided into four groups and received placebo, high-dose (500 mg/d) of RV (HRV, n = 40), middle-dose (250 mg/d) of RV (middle dose RV (MRV), n = 40) and low-dose (125 mg/d) of RV (low dose RV (LRV), n = 40) with orally administration. All patients received an 8-week treatment. The periodontal status of patients with periodontitis was recorded by using clinical attachment level (CAL), bleeding index (BI), oral hygiene index-simplified (OHI-S), and probing pocket depth (PPD). The levels of inflammatory markers in serum and gingival crevicular fluid (GCF), and systemic levels of endotoxin were evaluated using high sensitivity enzyme-linked immuno sorbent assay. Results: Outcomes showed that symptoms of periodontitis determined by CAL, BI OHI-S and PPD were improved by RV compared to placebo. RV treatment decreased inflammatory markers in serum and GCF compared to placebo in patient with periodontitis. Systemic endotoxin declined more in the RV group than the placebo-treated group. Conclusion: In conclusion, data in the current study indicate that RV is an efficient drug for the treatment of patients with periodontitis. The findings of the present study find that RV inhibits systemic local inflammatory markers and systemic endotoxin and suggest that 500 mg/d RV is the ideal dose for patients with periodontitis.